2020
DOI: 10.1128/mra.00892-20
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Pseudomonas putida BS3701, a Promising Polycyclic Aromatic Hydrocarbon-Degrading Strain for Bioremediation Technologies

Abstract: The strain Pseudomonas putida BS3701 was isolated from soil contaminated with coke by-product waste (Moscow Region, Russian Federation). It is capable of degrading crude oil and polycyclic aromatic hydrocarbons (PAHs). The P. putida BS3701 genome consists of a 6,337,358-bp circular chromosome and two circular plasmids (pBS1141 with 107,388 bp and pBS1142 with 54,501 bp).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Plasmid DNA isolation has revealed that seven of the effective Rhodococcus strains studied carry plasmids ranging in size from 20 to 1000 bp, and two strains carry two plasmids of 150 and 300 bp ( Figure 1 ). BS3701 has previously been shown to contain two plasmids of 56 and 100 bp [ 9 ]. A. baumannii 7 cells carry small plasmids (6, 12, 20, 42, and 50 kb) [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid DNA isolation has revealed that seven of the effective Rhodococcus strains studied carry plasmids ranging in size from 20 to 1000 bp, and two strains carry two plasmids of 150 and 300 bp ( Figure 1 ). BS3701 has previously been shown to contain two plasmids of 56 and 100 bp [ 9 ]. A. baumannii 7 cells carry small plasmids (6, 12, 20, 42, and 50 kb) [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas alloputida strain BS3701 contains two plasmids (pBS1141 and pBS 1142). Plasmid pBS1141 carries naphthalene biodegradation genes [ 9 ]. R. qingshengii F2-2 contains plasmids harboring genes of n -alkane biodegradation [ 10 , 11 , 12 , 13 ].…”
Section: Figurementioning
confidence: 99%
“…Однако до настоящего времени гены МБЛ P. putida искали только среди внутрибольничных штаммов [7][8][9][10]. В геноме штаммадеструктора компонентов нефти P. putida BS3701 [11] аннотировано 7 генов, ко дирующих белки семейства МБЛподобных металло гидролаз: 6 из них имеют хромосомную локализацию, 1 имеет плазмидную локализацию [12].…”
Section: Introductionunclassified